Noble Metal Based Alloy Nanoframes: Syntheses and Applications in Fuel Cells - Nosheen, Farhat; Anwar, Tauseef; Siddique, Ayesha; Hussain, Naveed (Frontiers in Chemistry, 2019)
Noble metal nanostructures are being used broadly as catalysts for energy conversion in fuel cells. To overcome the future energy crises, fuel cells are anticipated as clean energy sources because they can be operated at low temperature, their energy conversion is high or carbon release is almost zero. However, active or stable electrocatalysts are essential for the electrochemical reactions in fuel cells. Therefore, properties of the nanostructures greatly dependent on the shape of the nanostructures. Individual as well as interaction properties are greatly affected by the change in the surface area of the nanostructures. By shape controlled synthesis, properties of the nanostructures could be further enhanced by increasing the surface area or active sites for electrocatalysts. Therefore, an efficient approach is needed for the fabrication of nanostructures to increase their efficiency, activity or durability in fuel cells by reducing the usage of noble metals. Different types of hollow nanostructures until now have been prepared including nanoboxes nanocages, nanoshells and nanoframes etc. Nanoframes are the hollow unique three-dimensional structure which have no walls they only contain corner or edges so they have large surface area. In electrocatalytic reactions, the molecule involved in the reaction easily can reach the inner surface of the nanoframes thus noble metals utilization efficiency increases. Nanoframes usually have high surface area, greater morphological and compositional stabilities, allowing them to withstand in harsh environmental conditions. By considering the current challenges in fabrication of noble metal based alloy nanoframes as electrocatalysts, this review paper will highlight recent progress, design and fabrication of noble metal alloy nanoframes through different strategies mainly kirkendall effect, galvanic replacement, chemical etching and combination of both. Then electrochemical applications of nanoframes in fuel cells towards formic acid, methanol, ethanol as well as oxygen reduction reaction will also be highlighted. Finally, we will summarize different challenges in the fabrication of highly proficient nanocatalyst for the fuel cell with low cost, high efficiency or high durability which are the major issues for the highly commercial use of fuel cells in future.